Influence of composition and sintering temperature on density for pure and titanium alloy foams - Ahmad, Sufizar (Universiti Teknologi Malaysia, 2014)
Metallic foams with high fraction of porosity have gained their usefulness and are now becoming a new class of materials for various engineering applications. Due to this, the present work aims to produce pure titanium and alloy titanium foams with high density using different composition and sintering temperature. The slurry method is selected to produce the pure titanium and alloy titanium foam. The titanium slurry is prepared by mixing pure or titanium alloy powder, polyethylene glycol (PEG), methylcellulose and water. Polyurethane (PU) foam is then impregnated in the slurry and dried at room temperature. This is later sintered in a high temperature vacuum furnace with different sintering temperatures. The density of the samples was tested using Archimedes test. From the result of analysis of variance, composition and sintering temperature affect the density of the samples for pure and titanium alloy foams. The suitable compositions of pure and alloy titanium are 60 wt%, 65 wt%, 70 wt% and sintering temperatures are 1200°C, 1250°C and 1300°C to produce a high density for the pure and titanium alloy foams.